An evaluation of the Nelson Mandela Metropole as a location to attract investment - Nonxuba, Philile Zipho (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2006)
The Nelson Mandela Metropole is the largest contributor to the Eastern Cape Province's economy and its share of the production of the Eastern Cape is about 41, 3 % per annum. This requires that the competitiveness of the Metropole be improved in order to enable it to meet the challenges of the Province. The objective of the GEAR policy strategy places a focus on the leading coastal industrial locations of South Africa. Furthermore, the national government has shifted the responsibility of service delivery to local governments in an effort to reinforce the integrated development planning process in municipalities. To meet those challenges, the Metropole has focused its attention on improving local resources. To enhance the performance of the manufacturing industry of the Metropole, it is necessary to ensure that the Metropole has locational attributes to attract new investment. Such attributes include creation of closely located industries. This will help the firms to engage in competition as well as engage in co-operative activities among themselves. The study employs a variety of theories to highlight the need to enhance productivity of industries in order to attract new investment. These theories include the new (endogenous) growth theory that argues that productivity growth is determined by introduction of new technologies. Such technologies accrue because ideas that contribute to their development are nonrival, and thus their creation has a fixed cost and zero marginal cost. The property of fixed cost in the creation of ideas results in the emergence of increasing returns to scale. The Porter's Diamond framework is used in the study to take the issue of productivity growth further. Its thrust is that in particular nations some industries experience high productivity growth rates. It further argues that the locational attributes are responsible for these industries in registering high productivity growth levels. These attributes include the creation of advanced resources such as a skilled labour force. The data obtained from the survey of the research on the manufacturing industries forms part of this study. The findings of the survey reveal that although the manufacturing sector of the South African region has registered some significant success, there is still some room for improving its competitiveness. It revealed that development of the local markets through competition and cooperation among the industries would help to render these industries internationally competitive. This study concludes with some recommendations. These recommendations place emphasis on improvement of infrastructure, quality of labour force, and development of the region's market. In order to carry out the recommendations effectively, government policy has to be repositioned so as to enhance its visibility among the stakeholders in the economy. Of importance is to ensure the promotion of policy that supports geographically concentrated businesses.
Keywords: Nelson Mandela Metropolitan Municipality (Eastern Cape, -- South Africa); Nelson Mandela Metropolitan Municipality (Eastern Cape, -- South Africa) -- Economic conditions; Economic development -- South Africa -- Eastern Cape; Manufacturing industries -- South Africa -- Eastern Cape; Business enterprises -- South Africa -- Eastern Cape; Investments -- South Africa -- Eastern Cape